New genus, two new species and new records of subterranean freshwater snails (Caenogastropoda; Cochliopidae and Lithoglyphidae) from Coahuila and Durango, Northern Mexico - Alexander Czaja; Gabriel Fernando Cardoza-Martínez; Iris Gabriela Meza‑Sánchez; José Luis Estrada-Rodríguez; Jorge Saenz‑Mata; Jorge Luis Becerra-López; Ulises Romero-Méndez; Josué Raymundo Estrada‑Arellano; Miguel Ángel Garza-Martínez; José Antonio Dávila Paulín (Subterranean Biology, 2019)
This paper describes a new genus, two new species and new records of subterranean gastropods from the Sabinas and Álamos River, Coahuila, and the Nazas River, Durango, in northern Mexico. Phreatomascogos gregoi gen. n. et sp. n. from Don Martín Basin, Coahuila, is described based on shells and opercula that show some morphological similarities with shells of Phreatodrobia Hershler & Longley, 1986 (Lithoglyphidae), which is a subterranean genus from neighboring area in Texas, United States. Conchologically, the new genus can be distinguished from Phreatodrobia and all other subterranean genera by a unique combination of characteristic shell morphology and opercula apomorphies. Balconorbis sabinasense sp. n. (Cochliopidae) is the second species of this genus, which was previously known only from caves and associated subterranean habitats in Texas. The new record of Coahuilix parrasense, Czaja, Estrada-Rodríguez, Romero-Méndez, Ávila-Rodríguez, Meza-Sánchez & Covich, 2017 (Cochliopidae) from Durango and Coahuila is the first record of extant member of this genus out of its hitherto known habitat in the Cuatro Ciénegas basin, Coahuila. These records are remarkable because C. parrasense had been described recently as a fossil species. Shell morphologies of the new subterranean snails could be interpreted as possible evolutional adaptations to different hydrodynamic and other specific conditions in their habitat.